(untitled) (Interdisciplinary Studies Journal, 2025)
This article aims to discuss the role of education in promoting citizenship and democracy in the context of Vocational and Technological Education, as well as presenting an educational product developed with the aim of enabling students to become citizens who are aware of their rights and duties. The article explores how democracy, citizenship and democratic management can be stimulated in school environments, promoting a more critical citizen education. The research was carried out with integrated high school students at the Federal Institute of São Paulo, Campus Itapetininga, and involved the application of an educational product structured around a talk and an electoral simulation, aimed at raising awareness of issues related to democratic and participatory management. The methodology included questionnaires to assess the impact of this educational product on students’ understanding of these issues. The results indicate that the approach applied contributed to the development of citizens who are more aware of their rights and duties and ready to act responsibly in society.